LUDIC RESOURCES AND ITS IMPACT ON THE SPEAKING ABILITY IN ENGLISH LANGUAGE ON THE 8TH GRADE STUDENTS OF BASIC EDUCATION AT "EL CARMEN" EDUCATION UNIT, EL CARMEN, MANABÍ, 2017-2018 ACADEMIC PERIOD. - CHUMO MUÑOZ, ALEX JAVIER (2018)
LUDIC RESOURCES IS A BROAD TOPIC AND AT THE SAME TIME COMPLEX AS IT RELATES TO THE NEED OF HUMAN BEINGS TO COMMUNICATE, FEEL, EXPRESS AND PRODUCE A RANGE OF EMOTION ORIENTED ENTERTAINMENT, AMUSEMENT AND RECREATION IN HUMANS THAT LEAD US TO ENJOY, LAUGH AND EVEN CRY WHEN AN ENVIRONMENT THAT GENERATES EMOTIONS IS PROVIDED.